2019
DOI: 10.1111/capa.12321
|View full text |Cite
|
Sign up to set email alerts
|

L'élaboration et la mise en œuvre des recommandations issues d'évaluations de programmes au gouvernement du Canada

Abstract: Sommaire Au gouvernement du Canada, les rapports d'évaluation de programmes contiennent des recommandations qui visent l'amélioration de leurs modalités et de leur mise en œuvre. L'élaboration de recommandations peut constituer une étape laborieuse de la démarche évaluative et mobiliser plusieurs parties prenantes. Cependant, peu d'études ont été réalisées afin de déterminer comment ces recommandations sont élaborées et si elles sont ensuite mises en œuvre par les responsables des programmes. Cet article prése… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Such examples include Bourgeois and Maltais’ (2023) review of policy compliance as well as Bourgeois et al (2013) validation study of an EC measurement instrument for federal government organizations. A survey of Heads of Evaluation (directors and directors general supervising departmental evaluation units), conducted in 2018, revealed that overall, departments and agencies have the required tools and competencies (3.5/4, n = 22); and that federal evaluators have access to the required tools (3.25/4; n = 22), financial resources (3/4; n = 21); and policies and procedures (2.95/4; n = 22) to conduct high-quality evaluations (Bourgeois and Leblanc, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such examples include Bourgeois and Maltais’ (2023) review of policy compliance as well as Bourgeois et al (2013) validation study of an EC measurement instrument for federal government organizations. A survey of Heads of Evaluation (directors and directors general supervising departmental evaluation units), conducted in 2018, revealed that overall, departments and agencies have the required tools and competencies (3.5/4, n = 22); and that federal evaluators have access to the required tools (3.25/4; n = 22), financial resources (3/4; n = 21); and policies and procedures (2.95/4; n = 22) to conduct high-quality evaluations (Bourgeois and Leblanc, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Each case was developed using secondary EC or evaluation project data collected through document reviews, key informant interviews, and EC assessments, obtained as part of previous studies of individual and organizational EC (e.g. Bourgeois and Buetti, 2019; Bourgeois and Cousins, 2013; Bourgeois and Leblanc, 2019). These studies were conducted in recent years and focused on describing existing EC and evaluation practice in each group of organizations.…”
Section: Methodsmentioning
confidence: 99%